2020
DOI: 10.1038/s41598-020-64081-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition from spiral wave chimeras to phase cluster states

Abstract: Photochemically coupled Belousov-Zhabotinsky micro-oscillators are studied in experiments and simulations. Generally good agreement between the experimental and simulated dynamical behavior is found, with spiral wave chimeras exhibited at small values of the time delay in the coupling between the oscillators, spiral wave core splitting at higher values, and phase cluster states replacing the spiral wave dynamics at the highest values of the time delay. Spiral wave chimera dynamics is exhibited experimentally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recently, it has shown that chimera states may also exit in the human brain under some conditions such as epileptic seizures [43]. Chimera states are not only observed in one dimensional systems [1] but also in two or three dimensional systems [40,41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. One of the most remarkable examples in the two dimensional system is the so-called spiral wave chimera which combines the features of spiral waves and chimera states [39][40][41][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has shown that chimera states may also exit in the human brain under some conditions such as epileptic seizures [43]. Chimera states are not only observed in one dimensional systems [1] but also in two or three dimensional systems [40,41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. One of the most remarkable examples in the two dimensional system is the so-called spiral wave chimera which combines the features of spiral waves and chimera states [39][40][41][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Chimera states are not only observed in one dimensional systems [1] but also in two or three dimensional systems [40,41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. One of the most remarkable examples in the two dimensional system is the so-called spiral wave chimera which combines the features of spiral waves and chimera states [39][40][41][46][47][48][49][50][51][52][53][54][55][56][57]. Differing from the classic spiral wave whose core center is a phase singularity (or topological defect) at which the amplitude drops to zero, the core region of the spiral wave chimera consists of a group of desynchronized oscillators running at full amplitude [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the appearance of such exotic chimera patterns was verified theoretically in a handful [70][71][72][73][74][75] of RD and non-RD systems. Apart from these studies, there exist some experimental evidences [76][77][78] which reveal the emergence of spiral chimera states in coupled Belousov-Zhabotinsky chemical oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is shown that despite of the incoherent inner core, spiral wave is propagating stably in the outer region. Discovered by Shima and Kuramoto in 2004 in nonlocally coupled periodic oscillators [39], SWC has received growing interest in the field of nonlinear science in recent years, particularly for researchers working on pattern formations in reaction-diffusion (RD) systems [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. For the model of nonlocally coupled phase oscillators, an analytical description of SWC has been given in Ref.…”
Section: Introductionmentioning
confidence: 99%